PENANAMAN KARAKTER NASIONALISME DI PONDOK PESANTREN SALAFI - Sumarsih Anwar (Penamas, 2021)
Islamic boarding schools as part of the education system have an important role and their presence is continuously needed in growing the values of the character of nationalism. In its development, there are 2 (two) types of Islamic boarding schools, namely Salaf and Salafi. Salafi Islamic boarding schools tend to have a Wahabi edeology and are known as â€œRadicalâ€ Islamic movement. The Darul Sunnah Al Atsary boarding school in Bekasi has different face, although it has a salafi characteristic, the cultivation of the character of nationalism continues to be carried out and development. The leadership is of the view that inculcating the character of nationalism for santri is very important. This is in accordance with religious teachings, that loving the country is part of faith and every muslim is obliged to have it. The approach is applied through habituation, indoctrination (clear and consistent rules), clarification (discussing about the good or bad things), role models from leaders and educators by placing themselves as facilitators, leaders, and parents and even places to rely on trust, as well as helping others to reflect. The form of activities for cultivation the character of nationalism is routine and temporary. Data were obtained through observation, interviews and documentation.